Study of the temporal evolution of whitening in teeth undergoing mouthwashes using digital image processing (Revista de Investigaciones Universidad del Quindío, 2016)
Currently, many patients are interested in esthetic dentistry treatments for various reasons: from the search for personal satisfaction, up to needs labor type. The esthetic dentistry reference in our society is determined by several factors, including one that produces more dissatisfaction is abnormal tooth color or that does not meet the patient's expectations. For this reason it has been designed and implemented an algorithm in MATLAB that captures, digitizes, pre-processing and analyze dental imaging by allowing to evaluate the degree of bleaching caused by the use of mouthwash. The samples analyzed were human teeth extracted, which were subjected to different concentrations of mouthwash of several brands or manufacturers that offer teeth whitening when using these products, different concentrations of hydrogen peroxide were also used because this is the component prin- cipal in whitening products.
Keywords: Image Processing; Tooth Whitening; Human Teeth; Esthetic Dentistry